Formulasi dan Evaluasi Liposom Krim Ekstrak Daun Ubi Jalar Ungu (Lpomoea Batatas L.) - Sugindro Sugindro; Asri Anjeliani; Dedy Ma'ruf; Taufiq Dalming; Alamsyah Alamsyah (Jurnal Kesehatan Amanah, 2025)
Liposomes are good carriers that can be used to reduce toxic effects, increase drug effectiveness, increase the solubility of materials and permeability penetration of the compounds they carry, liposomes can also have potential as a system for controlling and targeting drug delivery. The aim of this research was to design a liposomal cream formula from purple sweet potato leaf extract (Ipomoea batatas L.) and to determine the quality of a liposomal cream preparation from purple sweet potato leaf extract (LPomoea batatas L.). The method used in this research uses a laboratory experimental method which aims to produce a liposomal cream preparation of purple sweet potato leaf extract (Ipomoea batatas L.).   Liposome preparations were made with a concentration of 1% purple sweet potato leaf extract, the results obtained were ball-shaped liposomes and some were oval-shaped, then the liposomes were used as an active substance to make cream with concentrations of 1%, 3% and 5%, then the liposomal cream formula was tested organoleptic, pH test, homogeneity test, spreadability test, adhesion test and stability test. The results of the stability test show that in F0, F1, F2 and F3 after storage at temperatures of 2°C and 35°C there was no change in the test. organoleptic, homogeneity test and pH test which means that the preparation is able to survive within the specified limits. However, in the test the spreading power of F0, F1, F2, and F3 experienced changes which meant that the preparation was not able to survive with a spreading power that remained within the specified limits.